Tech-Rich Instruction: Raising Students’ Awareness against Plagiarism in Academic Writing - Zaini Rohmad; Dewi Sri Wahyuni (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2018)
Plagiarism is an intolerant action in the circumstances of education; it is stealing or cheating any papers, ideas, and things related to someone’s works. This is a harmful offence with academic, professional, legal, and monetary consequences when someone is proved as a plagiarist. Students can be expelled from the class when they cheat colleagues’ works; the worst is that the university can retract their certificate of graduation when their manuscripts are investigated and proved as result of copying other works. Regarding to its danger, pla-giarism has to be avoided trough establishing curriculum in higher level of education. Teacher and lecturer should provide their lessons, especially in language skills, with awareness of the plagiarism danger to the students. A skill of language that most easily susceptible and detected in plagiarism is writing. Since writing is not a gift skill as listening, students need to learn how to write properly. Simply, when they are not able to rewrite someone’s statements with their own wording, students are doing plagiarism. This article reporting at a descriptive qualitative research aimed at describing the teaching method to raise students’ awareness toward the danger of plagiarism which is applied by a lecturer in Academic Writing Class of EED - UNS for the academic year 2016. She believes that when the students have awareness in the risks or consequences of plagiarism, they will act for not doing plagiarism in their works. She supports her conventional way of teach-ing with technology of plagiarism checker. The method of enrichment traditional teaching with technology is known as Tech-Rich Instruction (not blended learning). This Tech-Rich Instruction she applied is successful-ly raising her students’ awareness in the danger of plagiarism and leads to the efforts of avoiding plagiarism in academic writing.